Modern ceramic engineering properties, proceesing, and use in design - Richerson, David W. (Engineered materials, 1992)
Ceramic materials have proven increasingly important in industry and in the fields of electronics, communications, optics, transportation, medicine, energy conversion and pollution control, aerospace, construction, and recreation. Professionals in these fields often require an improved understanding of the specific ceramics materials they are using.